Petroleum science and technology : petroleum generation, accumulation and prospecting - Quddus, Muhammad Abdul (Petroleum engineer) (Boca Raton, FL : CRC Press/Taylor & Francis Group, LLC, 2021)
"This book focuses on petroleum generation, accumulation and prospecting describing natural hydrocarbon geology along with applicable aspects of physics, chemistry, biology, environmental science, mathematics and engineering/technology"--
1. Petroleum Pre-period Introduction 2. Petroleum Origin and Generation 3. Petroleum Migration and Accumulation 4. Petroleum Geological Survey 5. Petroleum Geophysical Survey 6. Petroleum Seismological Survey 7. Petroleum Geo-Electrical Survey 8. Petroleum Geochemical Survey
OCLC-licensed vendor bibliographic record.
Keywords: Petroleum engineering; SCIENCE / Earth Sciences / Geology; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Engineering / Civil